Paws for love [large type] - Mentink, Dana (Love unleashed, 2017)
The Only Thing Sweet About Jellybean Is His Name. Jellybean the terrier is about to unleash some serious mayhem on the unsuspecting town of Albatross. There's no quiet on the set when over-the-hill screen star Lawrence Tucker brings his naughty terrier, Jellybean, on location to the beachside town of Albatross, California. When Jellybean develops a rapport with Tucker's violin tutor, the painfully shy, socially awkward Misty Agnelli, her arm is twisted into minding the mischievous animal. Trailing Jellybean leads Misty into the candy store of Bill Woodson, a handsome chocolatier with a painful secret and a three-year-old niece to raise. Misty must deal with the unstable Tucker, a temperamental Jellybean, her budding feelings for the mysterious Bill, and the high-pressure atmosphere on the set. Though she wants nothing more than to flee, how can she tell her Grandma, Lawrence Tucker's biggest fan, that she abandoned the star and his dog? It's actors, animals, and antics galore when Jellybean gives his own heartwarming performance.